Hubungan Pengetahuan Dan Kepatuhan Ibu Hamil Konsumsi Tablet Tambah Darah Dengan Kejadian Anemia Di Kecamatan Leitimur Selatan Dan Teluk Ambon - Elpira Asmin; Armando Salulinggi; Christiana Rialine Titaley; Johan Bension (Jurnal Epidemiologi Kesehatan Komunitas, 2021)
Background: Anemia is a public health nutritional problem, especially for pregnant women. Anemia in pregnancy can adversely affect the morbidity and mortality of both mother and baby. According to the WHO, the prevalence of anemia in Indonesia was 40.5% in 2015, and 42% in 2016. One of the government's efforts to reduce the rate of anemia is the provision of iron tablets. In Indonesia, the coverage of giving at least 90 tablets during pregnancy in 2017 reached 80.81%. However, in Maluku Province, the coverage of iron supplementation (47.35%) was included amongst the four lowest provinces. This study aims to examine the relationship between pregnant women's knowledge and consumption of iron tablets and anemia in the Districts of South Leitimur and Teluk Ambon. Methods: This research is an analytical study with a cross-sectional approach. The subjects of this study were 165 pregnant women who were taken by purposive sampling.Result: The results showed 50.3% of pregnant women had anemia and only 21.8% complied with taking iron tablets. We found that there was no statistically significant association between pregnant women's knowledge of iron supplementation (p=0.443), as well as compliance with taking iron supplements (p=0.135), and anemia. Nevertheless, the percentage of women with anemia was lower in pregnant women who complied with taking iron supplements than those who did not comply. Conclusion : This study shows that efforts are still required to reduce the prevalence of anemia in Ambon City, including increasing women's compliance to take iron tablets.